(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The aim of the current research is to identify the impact of the media on the values and behaviors of university youth at Tartous University. The research followed the descriptive analytical method, and the field research was applied to a sample consisting of 200 male and female students from various university branches at Tartous University after a special questionnaire was prepared for this research (by the researcher), and its validity and reliability were confirmed by presenting it. A number of arbitrators and conducted a psychometric study. The research concluded that there is a non-significant correlation between the impact of the media on the values and behaviors of university youth at Tartous University. The results of the research found that male youth are more receptive to the media than female youth and are more influenced by values and behaviors. The research did not find any differences. On young people’s reception of media or its impact on their values and behaviors according to university specialization.